Optical and Structural Study of the CZTS (Cu2ZnSnS4) Thin Film for Solar Cell Derived from the Chloride-Based sol-gel Precursor Solution - Rahman, M; Bashar, MS; Islam, N (Dhaka University Journal of Science, 2022)
Fabrication of environmentally safe C2ZnSnS4 (CZTS) photovoltaic thin films of pure kesterite state is crucial. We have prepared CZTS thin films by sol-gel dip-coating process from chloride-based chemicals. After vacuum-annealed at 550°C, the optical and structural characters of the films were further examined by UV–vis spectroscopy, X-ray diffraction (XRD), scanning electron microscopy (SEM), and energy dispersive X-ray spectroscopy (EDS) methods. The CZTS films offered high optical absorption (0.4x104cm-1) and nearly optimum bandgap energy (1.65e V). X-ray diffraction examination confirmed the kesterite structure of films. Scanning electron micrograph affirmed the creation of jam-packed, condensed and granulated CZTS films. The thin film displayed intermittent disposal of agglomerated particles with clear-cut edges. The energy dispersive X-ray spectroscopy study gave the stoichiometric ratio as Cu: Zn: Sn: S= 2.2: 1.4: 1: 5.1. Dhaka Univ. J. Sci. 70(1): 1-7, 2022 (January)